Konflik Sosial Cerpen “Ama Tobi Diantara Batas Kampung Serumpun” Karya Silverster Petara Hurit (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to describe the social criticism of the short story "Ama Tobi di Antara Konten Batas Kampung Serumpun" by Silvester Petara Hurit. This study uses a qualitative method with data analysis using a sociology of literature approach. The results of the study indicate that there is social criticism of the short story "Ama Tobi di Antara Konten Batas Kampung Serumpun" by Silvester Petara Hurit, namely 1) Criticism of social relations. The social relations that are expected to live, grow and develop in the village of Lewolema, have now changed into a conflict that eliminates the values ​​of family, brotherhood, solidarity, cooperation between residents, 2) Criticism of identity starting from the change of the name of the village, can be considered as an effort to eliminate the cultural and historical identity of the community. In addition, the influence of colonialism, where the arrival of European missionaries and traders has brought changes in the value and belief system. The role of schools established by religious foundations has brought changes in the community's education system, and 3) Criticism of power is a struggle between traditional values ​​and modernity. Indigenous peoples have strong values ​​and traditions, but they also feel that they must adapt to the changing times and the presence of the government and religious foundation